2018
DOI: 10.6000/1929-2279.2018.07.03.2
|View full text |Cite
|
Sign up to set email alerts
|

Early Phase I Results for 4-Demethyl-4-cholesteryloxypenclo-medine [DM-CHOC-PEN] as Therapy in Adolescent and Young Adult (AYA) Subjects with Advanced Malignancies

Abstract: 4-Demethyl-4-cholesteryloxycarbonylpenclomedine (DM-CHOC-PEN) is a poly-chlorinated pyridine carbonate with a MOA via bis-alkylation of DNA @ N 7-guanine and N 4-cytosine that has completed adult clinical Phase I and II trials in individuals with malignancies involving the CNS. We report here objective clinical observations seen in a clinical Phase I DM-CHOC-PEN trial with AYA subjects that have cancer (some of which had CNS involvement). Subjects & Methods: DM-CHOC-PEN was administered as a single 3-hr IV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Table 1 reviews the results reported during Phase I/II clinical trial with DM-CHOC-PEN in primary brain tumors in adults [5,17]. Unfortunately, as noted in Table 1, DM-CHOC-PEN is not active in all GBMs treated to date [5,17]. During the trials, tumor tissue from several patients that received the drug were obtained and analyzed.…”
Section: Dm-choc-pen-mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 reviews the results reported during Phase I/II clinical trial with DM-CHOC-PEN in primary brain tumors in adults [5,17]. Unfortunately, as noted in Table 1, DM-CHOC-PEN is not active in all GBMs treated to date [5,17]. During the trials, tumor tissue from several patients that received the drug were obtained and analyzed.…”
Section: Dm-choc-pen-mechanism Of Actionmentioning
confidence: 99%
“…Thus, developing immune modulators that prevent impairment of cytotoxic lymphocytes is of potential importance and could be useful alone or with cytotoxic agents [1]. [5,17]; NED-no evidence of disease [5,17].…”
Section: Immunotherapy Targetsmentioning
confidence: 99%
“…++ DM-CHOC-PEN was administered IV once every 21-days; *No CNS disease -no responses; **CNS -CR, w/ peripheral progression The pharmacokinetic profile for DM-CHOC-PEN in the AYA subjects with a lower T 1/2 β -28:71 h reflects a 'healthier' metabolic profile for the drug compared with older adults, who may have been receiving medications for associated comorbidities resulting in induced hepatic metabolic activity (9). Moreover, AYA subjects-15-39 years old -are of major interest since they are not commonly enrolled in clinical trials and typically managed by pediatric and adult oncologists, rather than AYA oncology specialists who also appreciates the physical, psychosocial, emotional, sexual, spiritual, financial, dietary, etc.…”
Section: *No Cns Disease and No Responses; **Cns -Cr W/peripheral Progression; ***Liver Disease (Malignant Or Chronic)mentioning
confidence: 99%
“…Thus, DM-CHOC-PEN may be multifunctional -killing micrometastases, inhibiting DNA repair and inducing an 'abscopal' immune-type effect (7,8). The latter mechanism of action continues to be supported (9). peculiarities of this age group and, therefore apply specialized knowledge to their care (10,11).…”
Section: *No Cns Disease and No Responses; **Cns -Cr W/peripheral Progression; ***Liver Disease (Malignant Or Chronic)mentioning
confidence: 99%